α-Pinene isomerization to camphene: Effect of thermal treatment on sulfated zirconia - Comelli, Nora Alejandra (2006)
The isomerization reaction of α-pinene produces bicyclic and monocyclic compounds and other products. The purpose of this study is to investigate the influence of the pre-treatment temperature of the catalyst on the concentration of Lewis and Brönsted acid sites and the activity and selectivity of the catalyst. Catalyzed reactions in heterogeneous and homogeneous phases were performed. In heterogeneous reaction, sulfated zirconia (SZ) and pre-treated SZ catalyst at several temperatures were used. The thermal treatment affects the ratio between Brönsted and Lewis sites. Results were contrasted with those obtained with SZ catalyst without thermal treatment. In homogeneous reaction the catalyst is sulfuric acid, and in the reaction medium Brönsted sites are only present coming from the H+ of the acid. The ratio between bi/monocyclic compounds for H2SO4, SZ catalyst and pre-treated catalyst at several temperatures, SZ250, SZ350 and SZ500, varies between 0.4 and 4.3. It can be observed that there exists an optimal thermal treatment where the ratio is higher. FT-IR spectra of adsorbed pyridine on catalysts pre-treated thermally show the presence of Lewis and Brönsted acid sites. The amount of acid sites was determined by TPD of adsorbed pyridine.